Strategic investment decisions in multi-stage contests with heterogeneous players - Christian Deutscher; Marco Sahm; Sandra Schneemann; Hendrik Sonnabend (Theory and Decision, 2021)
When heterogeneous players make strategic investment decisions in multi-stage contests, they might conserve resources in a current contest to spend more in a subsequent contest, if the degree of heterogeneity in the current (subsequent) contest is sufficiently large (small). We confirm these predictions using data from German professional soccer, in which players are subject to a one-match ban if they accumulate five yellow cards. Players with four yellow cards facing the risk of being suspended for the next match are (i) less likely to be fielded when the heterogeneity in the current match increases and (ii) more likely to receive a fifth yellow card in the current match when heterogeneity in the next match increases or heterogeneity in the next match but one (when they return from their ban) decreases.
Keywords: 300; Tournaments; Multi-stage contests; Heterogeneity; Anticipating behaviour; Shadow effects